Minerals In The U.S. Economy: Ten-Year Supply-Demand Profiles For Mineral And Fuel Commodities (1965-74) (The National Institute for Occupational Safety and Health (NIOSH), 2012)
The accompanying supply/demand flow diagrams and 10-year tables for mineral and fuel commodities present essential data required by government, industry, and others to formulate policies and programs that can help assure an adequate and continuing supply of mineral raw materials. The 10-year data base terminates with 1974 figures because adequate world information was not available beyond that date. The selected mineral supply/demand tables and flow diagrams comprise but one "output" from the massive body of information and data collected and com-piled by the Bureau of Mines on a continuing basis covering mineral production, consumption, prices, shipments, imports, exports, and stocks, as well as industry activities in all States and abroad.